REPRESENTATIONS OF FOOD AND EATING IN FAST FOOD RESTAURANTS IN THE CITY OF SÃO PAULO: SOME ASPECTS ON HEALTH AND OBESITY - Collaço, Janine Helfst Leicht (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This text is derived from reflections raised over several researches in which undertook an effort to understand the relationship between eating out, food and urban life choices. In view of these previous results, I would like to explore data that were not worked and on that basis, I focused in representations of eating at food courts and health. Without exhausting the subject, I discuss some recurring elements observed in the speech of interlocutor’s standards and expectations; exposing some questions that guide my current questions about body, food and health.